Faktor-faktor yang mempengaruhi kebijakan dividen pada perusahaan non keuangan di Indonesia - MEIRYANANDA PERMANASARI (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to examine the variables that influence dividend policy on non-financial companies in Indonesian and to get the empirical evidence whether variables being respectively examined were financial performance, firm size, financial leverage, board independence, free cash flow, firm growth, liquidity, earnings per share, and net profit margin. Dividend payout ratio was used as proxies of dividend policy. The population of this research is 413 non-financial companies. Sampling techniques that used in this research is purposive sampling. There are 73 non-financial companies listed from 2010 to 2012 which met the criterion used as sample. Analysis method of this research is multiple regressions. The result of this research conclude that financial performance, firm size, free cash flow, firm growth, and earnings per share have influence toward dividend policy. Other variable such as financial leverage, board independence, liquidity, and net profit margin don’t have influence to dividend policy.